(untitled) (ҚазҰУ Хабаршысы. Математика, механика, информатика сериясы, 2018)
The problem of analysis of functional and organizational structure of logistics warehouse is considered in this article and a new technology for performing such analysis is offered. The technology is based on simulation modeling. In detail this technology includes methods and tools for development of simulation models, for creating problem-oriented services of the simulation modeling, for intelligent management of computing in a distributed environment. The aim of research is to develop and realize high-level methods and tools of formulating and solving non-traditional (for conventionally used warehouse management systems) tasks using problem-oriented knowledge. The example of methods and tools realization to automate the simulation modeling of the logistics warehouse is presented here. Experiments results for some tasks of the simulation modeling of the logistics warehouse are discussed.